3-Hydroxy-2-(hydroxymethyl)pyridinium chloride - Betz, Richard (International Union of Crystallography, 2011)
The cation of the title compound, C(6)H(8)NO(2) (+)·Cl(−), is essentially planar (r.m.s. deviation = 0.0104 Å). Intermolecular O—H⋯Cl and N—H⋯Cl hydrogen bonds, as well as C—H⋯O contacts, connect the molecules in the crystal structure. A short C⋯C distance of only 3.3930 (19) Å between C atoms of neighbouring rings is indicative of π-stacking. The corresponding centroid–centroid distance between the two aromatic systems is 4.2370 (7) Å due to the small overlap of the adjacent rings.